Analisis Arus Kas Operasi Dan Laba Akuntansi Serta Pengaruh Terhadap Return Saham (Studi Empiris Pada Perusahaan LQ-45 Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021) - Sari Oktavia Br Sihite; Adanan Silaban; Berliana Lumban Gaol (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of operating cash flow and accounting profit on the stock returns of LQ-45 companies listed on the Indonesia Stock Exchange for the period 2019-2021. The independent variable on research are operating cash flow and accounting profit, while dependent variable is the stock returns. This study includes a sample of 60 observations using purposive sampling method. Technical data analysis in this study using the SPSS 25 computer program. The result of this study showed that the variable operating cash flow and variable accounting profit has a positive significant effect on the stock returns. In addition, based on the coefficient of determination test, operating cash flow and accounting profit are able to explain their effect on the stock returns of 65,2%. Keyword: Operating Cash Flow, Accounting Profit, Stock Returns